2015
DOI: 10.1016/j.rbo.2013.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Estudo radiográfico dos aspectos anatômicos do fêmur proximal dos adultos brasileiros

Abstract: r e v b r a s o r t o p . 2 0 1 5;5 0(1):16-21 w w w . r b o . o r g . b r Artigo Original informações sobre o artigo Histórico do artigo: Recebido em 30 de outubro de 2013 Aceito em 5 de dezembro de 2013 On-line em 23 de janeiro de 2015 Palavras-chave: Fêmur/anatomia e histologia Fêmur/fisiologia Radiografia r e s u m o Objetivo: Verificar a geometria do fêmur da população brasileira por meio de estudo radiográfico e correlacionar os valores quanto ao sexo e ao lado direito/esquerdo. Métodos: Foram analisadas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The length of the neck of the femur was the only variable for which no significant difference between sexes was found. Analyzing radiographs of the proximal femur, de Farias et al (2015) demonstrated differences between males and females regarding the width and length of the neck, length of the femoral axis and neck-diaphyseal angle. The authors found larger values for males (38.54 mm ± 4.72 mm, p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…The length of the neck of the femur was the only variable for which no significant difference between sexes was found. Analyzing radiographs of the proximal femur, de Farias et al (2015) demonstrated differences between males and females regarding the width and length of the neck, length of the femoral axis and neck-diaphyseal angle. The authors found larger values for males (38.54 mm ± 4.72 mm, p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%